Exposure or expert? Setting standards for postgraduate education through a Delphi technique. Issue 9 (18th August 2006) - Carley, S; Shacklady, J; Driscoll, P; Kilroy, D; Davis, M
Abstract : Objectives: The aim of this study was to determine if a syllabus of upper limb anatomy for emergency clinicians composed by an expert panel reflected clinical practice as experienced by those at whom the syllabus would be directed. Methods: A three round Delphi study was performed using an expert group. We compared this with a measure of the exposure to anatomical concepts in the day to day practice of trainees in emergency medicine. Results: In total, 404 separate anatomical facts relating to the upper limb were reviewed by both groups. There was poor agreement (κ = 0.348) between the expert group and the trainees. Conclusion: We have shown disparity between what an expert group believes trainees should know and what trainees are actually exposed to in clinical practice. We believe this demonstrates that curriculum development must strike a balance between important (expert) and common (exposure) information. We have shown how an expert:exposure matrix may be used to inform curriculum development.